The effect of holes parameter on the properties of super-fast dried oil palm lumber (OPL) - Ramli, Farid (2019)
“Super-Fast Drying” is a new oil palm lumber (OPL) drying method which involve drilling holes and 2-step drying which is hot pressing and oven drying. From previous study, this technique could increase the drying rate of OPL with least defects. However, the method is still in preliminary phase. In this study, the best holes parameters for the OPL were verified. OPL were cut to the size of 300 x 50 x 20 mm, followed by holes drilling with the holes distance of 1.5 and 2.0 inch and holes depth of 1/3, 1/2, 2/3 and full depth. The specimens were hot pressed and oven dried. Mechanical and physical testing was carried out to determine the optimum parameters that show the best properties of super-fast dried OPL. From the findings, holes depth showed significant effect on the properties, while holes distance does not. The optimum holes distance and holes depth are 2.0 inch and 1\3 depth, respectively.